Congenital Penil Lymphedema in a Preterm Neonate - Şahin Hamilçıkan; Emrah Can (Galenos Yayinevi, 2018)
Congenital penile lymph edema is a rare anomaly of unknown cause of the lymphatic vessels. Lymphedema is often the shortage of lymphatic collecting ducts, lymphatic hypoplasia, hyperplasia, as a result of aphasia or lymph node fibrosis associated with the pathological development of lymphatic vessels. Lymphedema is generally a permanent condition and surgical treatment is necessary. Here we present the case of a newborn at 26 weeks via caesarean section with congenital penile edema, and no detection of chromosomal anomalies.